2000
DOI: 10.1291/hypres.23.177
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Blood Pressure in Uygur, Kazakh and Han Elderly Subjects in China.

Abstract: The Uygur in Hotan (Xinjiang, China) are reported to have a long life expectancy.The purpose of this study was to clarify the relationship between variations in blood pressure (BP) and longevity. Cross-sectional surveillance was carried out in both Hotan and Barkol. The subjects were divided into five groups: 1. Uygur longevity subjects in Hotan (103 subjects, age >90 yr); 2. Uygur elderly subjects in Hotan (107 subjects, age 65-70 yr); 3. Han elderly subjects in Hotan (41 subjects, age 65-70 yr); 4. Kazakh el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
4
20
0
Order By: Relevance
“…5,6 In Xinjiang, the Uygur have been shown to have a lower prevalence of hypertension than the Han or Kazakh people, [7][8][9] and in the present study, the elderly Uygur subjects were less hypertensive compared with the general elderly Chinese population. The longevous Uygur subjects were also less hypertensive, so it seems that those who are less hypertensive have an advantage in terms of life expectancy.…”
Section: Centenarians and Hypertensionsupporting
confidence: 45%
“…5,6 In Xinjiang, the Uygur have been shown to have a lower prevalence of hypertension than the Han or Kazakh people, [7][8][9] and in the present study, the elderly Uygur subjects were less hypertensive compared with the general elderly Chinese population. The longevous Uygur subjects were also less hypertensive, so it seems that those who are less hypertensive have an advantage in terms of life expectancy.…”
Section: Centenarians and Hypertensionsupporting
confidence: 45%
“…Other studies have reported that the Uygur have a lower prevalence of hypertension than the Han or Kazakhs living in the same Region (3,4). However, the Uygur centenarians have been shown a higher incidence of hypertension than the Uygur individuals (aged 65-70 years, candidates for centenarians)…”
Section: Introductionmentioning
confidence: 95%
“…Despite a lack of medical treatment, the Uygurs living in the southern territory of the Xinjiang Uygur Autonomous Region of the People's Republic of China reportedly represent a naturally long-lived population. [1][2][3] Prevalence of hypertension is lower in Uygurs than in other any ethnic group in China. 1 However, our previous study noted that Uygur centenarians demonstrated higher blood pressure (BP) than other elderly subjects on occasional measurement.…”
mentioning
confidence: 96%
“…[1][2][3] Prevalence of hypertension is lower in Uygurs than in other any ethnic group in China. 1 However, our previous study noted that Uygur centenarians demonstrated higher blood pressure (BP) than other elderly subjects on occasional measurement. 4 A study of centenarians has shown that 24-h BP values were higher than office BP values, 5 but very limited numbers of centenarians have been studied.…”
mentioning
confidence: 96%